2020
DOI: 10.3390/ani10101861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Form and Level of Wheat Straw Inclusion on Growth Performance and Blood Metabolites of Fattening Goat

Abstract: The inclusion of straw in high concentrate total mixed rations (TMRs) of male fattening goats can provide the necessary fiber to prevent ruminal acidosis and maintain growth. The objective of this study was to evaluate the effects of the physical form (PF) of the diet (pelleted vs. conventional) and the straw level (SL) of wheat straw (WS) (15% versus 25%) in total mixed rations on feed intake, growth, total tract digestibility, and blood metabolites of fattening goats. Thirty-two male Beetal goats (27.4 ± 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…Growing crossbred Boer goats consumed 34% more pellets (P < 0.01) than mash-based diets (Table 2). These findings are consistent with research published by Malik et al (2020) which shown that goats given pelleted total mixture rations (TMR) consumed more dry matter (p<0.05) than goats fed chopped TMR. Growth performance is mainly determined by total feed intake and the total quantity of nutrients that animals can utilize per unit of ingested feed.…”
Section: Feed Intakesupporting
confidence: 92%
“…Growing crossbred Boer goats consumed 34% more pellets (P < 0.01) than mash-based diets (Table 2). These findings are consistent with research published by Malik et al (2020) which shown that goats given pelleted total mixture rations (TMR) consumed more dry matter (p<0.05) than goats fed chopped TMR. Growth performance is mainly determined by total feed intake and the total quantity of nutrients that animals can utilize per unit of ingested feed.…”
Section: Feed Intakesupporting
confidence: 92%
“…Hence, the observed CP content of natural pasture hay in the current study was lower than the maintenance requirements of sheep. This might be attributed to the late harvesting stage and forage species composition (Malik et al., 2020). Natural pastures in Ethiopia are managed in free grazing and subsequently the forage harvested like this is low in biomass and quality (Agza et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the late harvesting stage and forage species composition (Malik et al, 2020). Natural pastures in Ethiopia are managed in free grazing and subsequently the forage harvested like this is low in biomass and quality (Agza et al, 2013).…”
Section: Chemical Composition Of Treatment Feedsmentioning
confidence: 99%
“…Typically, ruminant diets are composed mainly of concentrates, silage, roughage, and other feed additives. In modern intensive production systems, roughage, which is mostly fibrous plant-derived feed ingredients, usually constitutes approximately 20%-60% of the dry matter weight in a conventional ruminant ration (Suaŕez et al, 2007;Malik et al, 2020;Yi et al, 2022). Thus, the characteristics and prices of roughage are not only the key determinants influencing the production performance and product quality of ruminants, but also the pivotal factors affecting livestock rearing profit.…”
Section: Introductionmentioning
confidence: 99%